2013
DOI: 10.1155/2013/967987
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 Expression in Dermatitis Herpetiformis and Bullous Pemphigoid

Abstract: Dermatitis herpetiformis (DH) and bullous pemphigoid (BP) are skin diseases associated with eosinophilic and neutrophilic infiltrations. Although cytokines are critical for the inflammatory process, there are single findings concerning concentration of IL-17 in bullous diseases. The goal of this study was to assess IL-17 expression in DH and BP patients. Skin biopsies were taken from 10 DH, 14 BP patients and from 10 healthy subjects. The localization and expression of IL-17 was studied by immunohistochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 43 publications
3
30
1
1
Order By: Relevance
“…Th17'den salınan IL-17A; multipl proinflamatuvar mediatörleri etkileyerek etkisini gösteren bir sitokindir 10 . Th17 hücre aracılı inflamasyonla ilişkili olarak otoimmün büllöz hastalıklar arasından büllöz pemfigoid ile ilişkisinin daha güçlü olduğuna dair kanıtlar mevcuttur 23,24 . Yaptığımız literatür taramalarında Th17 hücrelerden salınan IL-17A'nın PV ile ilişkisini araştıran çok fazla çalışmaya rastlamadık.…”
Section: Discussionunclassified
“…Th17'den salınan IL-17A; multipl proinflamatuvar mediatörleri etkileyerek etkisini gösteren bir sitokindir 10 . Th17 hücre aracılı inflamasyonla ilişkili olarak otoimmün büllöz hastalıklar arasından büllöz pemfigoid ile ilişkisinin daha güçlü olduğuna dair kanıtlar mevcuttur 23,24 . Yaptığımız literatür taramalarında Th17 hücrelerden salınan IL-17A'nın PV ile ilişkisini araştıran çok fazla çalışmaya rastlamadık.…”
Section: Discussionunclassified
“…Generated from Th17 cells, subset of T helper cells, IL‐17, induces expression of cytokines and chemokines (IL‐1β, GM‐CSF, G‐CSF, CXCL1, CXCL2) and MMP‐9 that facilitate granulocyte recruitment, activation and ultimately protease release that results in characteristic BMZ degradation . IL‐17 is elevated in BP patients’ serum and blister fluid and has been implicated in mediating tissue destruction . Recent experimental studies have identified that mouse models deficient in IL‐17a do not develop BP .…”
Section: Evolving Therapeutic Targetsmentioning
confidence: 99%
“…[158][159][160][161][162][163] IL-17 is elevated in BP patients' serum and blister fluid and has been implicated in mediating tissue destruction. [164][165][166] Recent experimental studies have identified that mouse models deficient in IL-17a do not develop BP. 167 Additionally, mice treatment with anti-IL-17a antibodies exhibited significantly reduced disease development.…”
Section: Epidermolysis Bullosa Acquisitamentioning
confidence: 99%
“…Its extracellular noncollagenous 16A (NC16A) domain harbours the major T-cell and B-cell epitopes. 63,64 Additional immune modulatory T-cell subsets, such as Treg cells and cd T cells, are significantly reduced in BP based on preliminary studies. 53,54 Most of the autoreactive, BP180-specific T cells exhibit a Th2 profile, 53,55 whereas BP180-specific peripheral T cells from healthy individuals are dominated by the Th1 type.…”
Section: Immunological Alterations In Bullous Pemphigoidmentioning
confidence: 99%
“…61,62 Elevated numbers of Th17 cells and IL-17A levels were observed in the skin lesions of patients with BP, and a potential involvement in BP was therefore assumed. 63,64 Additional immune modulatory T-cell subsets, such as Treg cells and cd T cells, are significantly reduced in BP based on preliminary studies. [65][66][67] While the BP180-NC16A domain represents the immunodominant region for T cells, it is also targeted by IgG autoantibodies from patients with BP.…”
Section: Immunological Alterations In Bullous Pemphigoidmentioning
confidence: 99%